2020
DOI: 10.1177/0033294119899906
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mindfulness, Psychopathological Symptoms, and Academic Performance in University Students

Abstract: It has been shown that a mindfulness construct involving five component skills (observing, describing, acting with awareness, nonjudging of inner experience, and nonreactivity to inner experience) is related to well-being and lessens depression, anxiety, and stress symptoms. This study investigates the relationship between mindfulness, academic performance, and psychopathological symptoms in a sample of Swiss university students during preparation for examinations. A total sample of 150 university students fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
1
16
0
5
Order By: Relevance
“…Nonetheless, and by way of example, there is growing recognition that mindfulnessbased interventions could play a determining role in addressing some of these factors among university students [32]. A randomized controlled trial showed that mindfulness training could improve problem-focused coping among Norwegian psychology and medical students [33].…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
“…Nonetheless, and by way of example, there is growing recognition that mindfulnessbased interventions could play a determining role in addressing some of these factors among university students [32]. A randomized controlled trial showed that mindfulness training could improve problem-focused coping among Norwegian psychology and medical students [33].…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
“…High levels of stress have been generally perceived by students, which have partly been attributed to interpersonal interaction pressure, life pressure, poverty, violence, especially academic pressure in school settings [1]. Incorporating schooling into one's daily life might be another source of stress, impairing academic performance and quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students' well-being has become a worldwide concern because they have been at risk of anxiety, loneliness, and stress [3]. Therefore, the above pressure perceived by students has significant negative impacts on students' mental health, even leading to psychological disorders and poor academic performance [1]. Mindfulness mediation has been applied to improve well-being and mental health to improve students' health status and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, the positive mental health model of graduate students was selected as the research variable for analysis. This model has three dimensions: positive emotional experience, good psychological quality and adequate social support [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%